Akad dalam Fiqih Muamalah - Ulinnuha, Ahsin Haris (Maliki Interdisciplinary Journal, 2024)
Akad is a term in Arabic that refers to an agreement or agreement between two or more parties. In the context of finance and Islamic law, contract often refers to an agreement or transaction carried out in accordance with sharia principles. Contracts are an important part of various types of Islamic economic transactions, such as buying and selling, renting, loans and investments. The main principle in a contract is a voluntary agreement between the parties involved, as well as the clarity and validity of the terms agreed upon in the agreement. In the contract, both parties must agree to the terms set and have a clear understanding of their respective rights and obligations. -each. This ensures that no party is harmed or unfairly taken advantage of in a transaction. Apart from that, contracts also have a spiritual dimension in Islam.